Perceptions about sexual abstinence and knowledge of HIV/AIDS prevention among in school adolescents in a western Nigerian city (2011)
Background: Young people are becoming increasingly exposed to the risk of HIV infection. According to the 2008 HIV/Syphilis sentinel survey in Nigeria, 3.3% of young people aged 15-19 years are infected. Primary prevention especially abstinence, remains one of the most realistic interventions for reducing further spread of the virus. However, the adoption of sexual abstinence as a prevention strategy among adolescents remains low and factors influencing its practice among urban young people in Nigeria are relatively unknown. The aim of the study was to document the sexual abstinence behaviour of in-school adolescents, the factors influencing or obstructing abstinence, and knowledge of HIV and AIDS in Ibadan, South-West Nigeria. Methods: The study was a descriptive cross-sectional survey of students in Ibadan South-West Local Government Area. A total of 420 respondents (52% males and 48% females), selected through a multistage sampling technique, completed a semi-structured questionnaire. This was supplemented with eight focus group discussions (FGDs) which had an average of 9 respondents within the 10 and 19 years age group. The data from the FGDs were transcribed and summarized manually while the quantitative data was analyzed using the Statistical Package for the Social Sciences to generate frequencies, cross tabulations of variables and logistic regression analysis. Results: Twelve percent of the entire sample had ever had sex. Overall, knowledge of HIV transmission and prevention was high and most respondents favoured the promotion of abstinence as an HIV prevention strategy. A smaller proportion of male respondents (79%) abstained compared with the females (98%). Major predictors of sexual abstinence were being a female, not having a boyfriend or girl friend, not using alcohol and having a positive attitude towards abstinence (P < 0.05). Sexual abstinence was also significantly associated with perceived self efficacy to refuse sex and negative perception of peers who engage in sexual behaviours (P < 0.05). Majority of the FGD discussants suggested the involvement of parents, media, schools, faith-based institutions and non governmental organizations in promoting the adoption of abstinence. Conclusions: The sexual abstinence behaviour of young persons is influenced by multiple factors and should be considered in determining the effectiveness of interventions targeting this behaviour. Coherent sexuality education interventions to promote the adoption of abstinence among young people are urgently needed.